Presumption of death law in Malaysia: the case of missing persons - Mohd Noor, Nor Azlina; Abd Aziz, Ahmad Shamsul (Future Academy www.FutureAcademy.org.UK, 2018)
The snags indispensable matters in managing the affairs of person who has disappeared and remained absent without explanation are both bountiful and thought-provoking. If it is not known whether a person is alive or dead, the status of his personal law remains uncertain and his properties are rendered virtually useless. At present, there is no specific legislation which deals with presumption of death in Malaysia despite of many cases had occurred in the past. To cater the issue, the judiciary has followed the common law doctrine of presumption of death rules to handle long-term unexplained absences. Therefore, this paper aims to examine the current legal framework of presumption of death in Malaysia. This article adopts the doctrinal analysis by examining the existing primary and secondary materials gathered from multiple sources including statutory, case law and other legal and non-legal literatures relating to the presumption of death in Malaysia. This article concludes that there are various laws that governed the matters relating to the missing person to be presumed dead. The variety of laws has constantly post hardship to the family members. For the Muslim, even though they have two options to choose, in reality they actually need to go to both court. Firstly, they need to attend the Syariah High Court to dissolve the marriage after the expiry of 4 years and secondly, they need to go to Civil High Court after another three years to settle the matters relating to estate administration.